1971
DOI: 10.1159/000121996
|View full text |Cite
|
Sign up to set email alerts
|

Transport Mechanisms and Thyroxine Uptake in Pineal Slices

Abstract: After a preliminary study showed conclusively that in vitro pineal cells avidly take up thyroid hormones but not iodide, a series of tissue slice studies using 125I-thyroxine were conducted to investigate the mechanism of thyroxine (T4) uptake in pineal cells. T4 uptake was unaffected by the presence or absence of glucose and cofactors, nor was uptake inhibited by cyanide. No binding capacity for T4 could be demonstrated, and the percent uptake of labelled T4 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1971
1971
1985
1985

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…There are a number of observations by other workers which also suggest that thyroxin affects cells in the pineal gland, main ly by enhancing pineal activity. Pineal tissue avidly takes up thyroid hormones both in vivo [29] and in vitro [4]. Indica tions that thyroid hormones may have an excitatory action on pineal hormone synthesis result from observations that administration of potassium iodide leads to pinealocyte hy perplasia and hypertrophy [14] and that thyroxin stimulates histochemically demonstrable enzymes of pinealocytes in vitro (13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of observations by other workers which also suggest that thyroxin affects cells in the pineal gland, main ly by enhancing pineal activity. Pineal tissue avidly takes up thyroid hormones both in vivo [29] and in vitro [4]. Indica tions that thyroid hormones may have an excitatory action on pineal hormone synthesis result from observations that administration of potassium iodide leads to pinealocyte hy perplasia and hypertrophy [14] and that thyroxin stimulates histochemically demonstrable enzymes of pinealocytes in vitro (13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, thyroid weight in creases following pinealectomy [6,27] and decreases after the administration of pineal substances in adult mammals [16], Since pineal tissue avidly takes up thyroid hormones both in vivo [29] and in vitro [4], it is logical to conclude that the pineal influence on the hypothalamo-hypophyseal-thyroid axis may be under feedback control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our investigation of thyroid-pineal interaction, we recently reported findings that suggest some form of mediated diffusion as the mechanism of T4 transport into pineal cells [Cady et al, 1971]. Our present study deals with the metabolism of T 4 by these cells.…”
Section: Abstract Pineal Thyroxine Metabolismmentioning
confidence: 83%
“…It has been demonstrated that the pineal takes up thyroxine (T4) in vivo [Ford and G ross, 1958] and in vitro [Cady et al, 1971]. As part of our investigation of thyroid-pineal interaction, we recently reported findings that suggest some form of mediated diffusion as the mechanism of T4 transport into pineal cells [Cady et al, 1971].…”
Section: Abstract Pineal Thyroxine Metabolismmentioning
confidence: 98%